THE REALITY OF EDUCATION IN THE LITHUANIAN RURAL COMMUNITY OF THE FIRST HALF OF THE 20TH CENTURY: EVERYDAY EDUCATION FOR EVERYDAY LIFE - Stonkuvienė, Irena (Acta Paedagogica Vilnensia, 2007)
The article discuses the ordinary reality of the education in the Lithuanian rural community of the first half of the 20th century. It also analyses the influence of daily physical and material environment on education and discusses the goals and objectives of education. The study is based on the material collected during ethnographic interviews carried out in the districts of Biržai, Kupiškis, Ignalina, Rokiškis, Šakiai, Kaišiadorys, Kretinga and Prienai. The research results revealed that the education reality of the period in question formed an inseparable part of the everyday life reality. Children education in the Lithuanian rural community of the first half of the 20th century was a continuous process, which occurred on a natural plane in the process child’s play, work and communication. The community in the Lithuanian rural regions laid a particular emphasis on the external (everyday, social and material) side of education reality. According to the respondents, the daily environment, which reflected people’s interrelations and their contacts with material world and living space, is the main factor differentiating the modern education from the one in the beginning of the 20th century. The simplicity, tidiness and functionality of the environment had a considerable effect on all the sides of people’s life, including their education as well. The sensitive relation with the environment and reflections of the sacrality in the use of everyday things, household utensils and food were characteristic of the majority of the families of the analysed period. The poverty and hardship, which accompanied the daily life of that period, were not always considered to be a factor, which impaired the quality of life and education. On the opposite, according to the respondents, the hardship only hardened the people, enabled them to cognise life, prompted people’s sensitivity, sympathy and willingness to help. However, in cases, when basic living conditions were not ensured (lack of main household utensils, food (especially bread), insufficient tidiness and cleanness), relations of people with both the environment and people surrounding them used to get complicated and sometimes there was a threat for survival of the most vulnerable members of the community, i.e. children. The realia of everyday life in the community were reflected by the goals and objectives of education, which focused on preparing of an individual for life in the community: perfect performing of duties in the life of community and family, involvement of an individual in the active religious life, etc. The goals, which were not related to the community life were not very supported. The ambitions of the growing generation to learn, change their life and escape from the rural routine or to significantly improve the life through application of the acquired knowledge, were also impeded by external conditions (the attitude of the sočiety to science, the social and financial status of the family, etc) and lack of internal motivation.